Механизмы сезонной цикличности размножения птиц. Сообщение I. Гипоталамический контроль развития и функции гонад - Новиков, Б.Г.; Руднева, Л.М. (Вестник зоологии, 1974)
The article deals with the results of studies in hypothalamic mechanisms of reproductive function regulation in birds. The problem of gonads prefunctional development, localization in hypothalamus structures, participating in hypophyseal gonadotropic func¬tion regulation, egg-shell formation and oviposition are considered. Basing on the results of the authors own investigations and the data from literature the inner mechanisms of season periodicity in birds reproduction are analysed.